THE LEVEL OF HADITHS QUOTED IN “KITOB AN-NIYAT” BY UMAR TIRMIDHI - Muhiddin Choriev (European Journal of Interdisciplinary Research and Development, 2023)
If we study the life and legacy of Umar Termizi. It is clear that he was a Sufi and a preacher. In the middle ages when Umar al-Tirmidhi lived, the tariqat was very developed in Mowaraunnah. This was one of the reasons why Umar Tirmidhi was a member of the sect. We will witness this if we analyze the hadiths mentioned in the “Kitob an-niyat” by Umar Tirmidhi. Umar Tirmidhi, like other Sufis, does not care about the authenticity or weakness of a hadith. The quoted hadiths represent the places of actual intention. Let’s analyze the hadiths that he quoted in his “Kitob an-niyat”.